A Tale of Two Cities - Dickens, Charles, 1812-1870.; Ablett, Barry (London : Usborne, 2009)
The classic story by Charles Dickens retold as part of the Usborne Young Reading Programme for children ready to tackle longer and more complex stories. Set during the French Revolution, the lives of Charles Darnay and his family are changed forever as the drama unfolds.
3-6.